Transcriptome Analysis of Poplar Under Salt Stress and Over-Expression of Transcription Factor NAC57 Gene Confers Salt Tolerance in Transgenic Arabidopsis - Yao, Wenjing; Zhao, Kai; Cheng, Zihan; Li, Xiyan; Zhou, Boru; Jiang, Tingbo (Frontiers in Plant Science, 2018)
NAC domain genes belong to a large plant-specific transcription factor family, which is well-known to be associated with multiple stress responses and plant developmental processes. In this study, we screened differentially expressed genes (DEGs) and detected mRNA abundance of NAC family by RNA-Seq in the poplar leaves under salt stress condition. A total of 276 up-regulated DEGs and 159 down-regulated DEGs were identified to be shared in Populus alba×Populus glandulosa and Populus simonii × P. nigra. Among 170 NAC members, NAC57 gene was significantly up-regulated in response to salt stress in the two species. Tissue-specific and salt-responsive analyses indicated the expression pattern of NAC57 gene was spatial and temporal in poplar under salt stress. Particle bombardment result showed subcellular localization of NAC57 was not solely nucleus-targeted. Full-length cDNA sequence of NAC57 gene was cloned from Populus alba×Populus glandulosa and transformed into Arabidopsis thaliana. Under salt stress, transgenic Arabidopsis overexpressing NAC57 showed higher seed germination rate, root length, and fresh weight than wild type plants. In addition, the transgenic plants displayed higher superoxide dismutase activity and peroxidase activity, and lower malondialdehyde content and relative electrical conductivity than the wild type under salt stress condition. Furthermore, histochemical staining indicated reactive oxygen species accumulation was lower in the transgenic plants than that in the wild type under salt stress. All the results indicated that the NAC57 gene plays an important role in salt stress responses.